2015
DOI: 10.5539/ijms.v7n2p10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effective Help for Social Anxiety: MMORPGs Delivering Online Help

Abstract: Most research discusses the characteristics of massive multiplayer online role-playing games (MMORPGs), few studies have applied MMORPGs to provide psychological and behavioral help. The purpose of this research is to explore the online help application of MMORPGs and ascertain their effectiveness in providing online help. Participants included 269 university students. The questionnaire demonstrated adequate validity and complements a Likert-type self-reporting measure of social anxiety, quality of life, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Scheier et al (1986) suggest that when people are exposed to situations where they fear they will behave inappropriately or embarrassingly because of their interpersonal skills, they try to substitute the social interaction by active use of alternative technological avenues, e.g. online socialization (Ho et al , 2015) or mobile phone text messaging rather than calling (Lee et al , 2014). Based on these, we argue that a non-native customer may engage in avoidance behavior in different ways based on their previous experiences at the focal ICSE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scheier et al (1986) suggest that when people are exposed to situations where they fear they will behave inappropriately or embarrassingly because of their interpersonal skills, they try to substitute the social interaction by active use of alternative technological avenues, e.g. online socialization (Ho et al , 2015) or mobile phone text messaging rather than calling (Lee et al , 2014). Based on these, we argue that a non-native customer may engage in avoidance behavior in different ways based on their previous experiences at the focal ICSE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, when people face situations where they fear they will behave inappropriately or embarrassingly because of their interpersonal skills, they try to substitute the social interactions with the active use of alternative technological avenues, e.g. online socialization (Ho et al, 2015) or text messaging rather than calling (Lee et al, 2014). Based on this discussion and the proliferation of smart services, we suggest that during ICSE, the interaction discomfort experienced by non-native customers based on the anticipated linguistic discrimination would make consumers opt for the avoidance mechanism, i.e.…”
Section: Interaction Comfortmentioning
confidence: 99%
“…A number of studies have shown advantages of web-based socialization and web-based peer support for patients with disorders such as autism [7,8], social anxiety disorder [9], and chronic conditions such as cystic fibrosis (CF), where the danger of cross-infection of respiratory tract bacteria [10][11][12] prevents patients with CF from socializing in person.…”
Section: Introductionmentioning
confidence: 99%